PENDIDIKAN POLITIK BAGI PEMILIH PEMULA OLEH PARTAI POLITIK DI KABUPATEN KEPULAUAN MERANTI BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK - Sri Kemuning; Maria Maya Lestari; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Political parties have a role in providing political education as stated in law number 2of 2008 concerning political parties. Political education is very important for society,especially for beginner voters, considering that beginner voters are emotionally unstable andhave minimal political knowledge.This type of research is empirical (sociological), which uses empirical facts taken fromKPU and high school data as well as interviews with political parties and first-time voters.The problem that the author raises is how to provide political education for beginnervoters in Meranti Islands Regency based on law number 2 of 2008, what are the supportingand inhibiting factors in providing political education for beginner voters in Meranti IslandsRegency, and what efforts to increase community participation especially new voters inMeranti Islands Regency in politics.The results of the research show that in Meranti Islands Regency political parties aresaid to not be running optimally and there are still shortcomings. It can be said that most ofthe political parties in the Meranti Islands Regency only focus on providing political educationto cadres or internal party members without involving the community, especially first-timevoters. The inhibiting factor for Political Parties in Kepuluan Meranti Regency in providingpolitical education is the public's distrust of Political Parties, that when participating inpolitical party events people think they will be said to be members of a Political Party. Lack ofenthusiasm from the public. And several political parties said that there were no obstacles, butpolitical education was not being implemented in the community. This means that there is alack of understanding of Political Party administrators in their function and role in providingpolitical education to the community. Author's suggestion: It is hoped that there will be anoversight institution for Political Parties in carrying out their roles and responsibilities toprovide political education, and it is hoped that Political Parties can implement the rules,duties, functions and authority of Political Parties in providing political education inaccordance with the updated Law Number 2 of 2008 again becomes Law Number 2 of 2011concerning Political Parties. And it is hoped that there will be real action from political partiesand the government, so that people are not anti-politics and it does not become a trust issuefor political parties.Keywords: novice voters, political parties, political education.